12.9k views
2 votes
how do i solve the system of equations negative x minus y equals 0 + 6 x - 5 y equals 66 by combining the equations

User Jud
by
4.7k points

1 Answer

1 vote

Question

-x - y = 0

6x - 5y = 66

Step one, name the two equations

-x -y = 0 .................................................1

6x - 5y = 66 ..............................................2

Step 2, choose one of the equation, make one of the variable subject of formula and substitute in the second equation.

-x - y = 0

y = -x

Subtitute y in equation 2

6x - 5(-x) = 66

6x + 5x = 66

11x = 66

divide through by 11

x = 66/11

x = 6

since y = -x

y = -6

User Guard
by
5.3k points